2014
DOI: 10.1016/j.tox.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxylamine reactivity kinetics as an amine based nucleophile for screening electrophilic dermal sensitizers

Abstract: Chemical allergens bind directly, or after metabolic or abiotic activation, to endogenous proteins to become allergenic. Assessment of this initial binding has been suggested as a target for development of assays to screen chemicals for their allergenic potential. Recently we reported a nitrobenzenethiol (NBT) based method for screening thiol reactive skin sensitizers, however, amine selective sensitizers are not detected by this assay. In the present study we describe an amine (pyridoxylamine (PDA)) based kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…The mechanistic and reactivity data presented here are essentially consistent with previously published data from peptide reactivity assays 30,[33][34][35][36][37]39 and hence demonstrate that the technique can be used to support the study of skin sensitization AOP chemicals within TT21C 1 approaches. Peptide reactivity assays are generally run over 24 h with the electrophile in excess, hence they differ from the NMR methodology described here in which reactions were generally followed for less than one hour and with excess nucleophile.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The mechanistic and reactivity data presented here are essentially consistent with previously published data from peptide reactivity assays 30,[33][34][35][36][37]39 and hence demonstrate that the technique can be used to support the study of skin sensitization AOP chemicals within TT21C 1 approaches. Peptide reactivity assays are generally run over 24 h with the electrophile in excess, hence they differ from the NMR methodology described here in which reactions were generally followed for less than one hour and with excess nucleophile.…”
Section: Discussionsupporting
confidence: 86%
“…24 The study of haptenation reactions has largely been restricted to the use of nucleophilic protein-mimetic models as the protein target is not always identified. [25][26][27][28][29] Indeed, several approaches for the assessment of chemical reactivity towards proteins have been developed, 22,[30][31][32][33][34][35][36][37][38][39] largely driven by the need to assess chemical reactivity in skin sensitization, although it should be noted that they are equally applicable wherever a covalent mechanism of action is involved in the MIE; they include spectrophotometric assays that monitor changes in UV absorbance and fluorescence 32,33 as well as peptide reactivity assays that measure reactivity of nucleophiles to synthetic peptides using HPLC-UV, MS and MS/MS platforms. 30,[34][35][36][37] These assays do, however, have some limitations which include providing limited mechanistic information and indirect reactivity data that are not suitable for risk modelling (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PM showed increased reactivity compared to lysine for MGO, but this enhanced reactivity was at least an order of magnitude less than what was seen with 1,4-dicarbonyls. Other investigators also found that the reaction rate of PM for compounds that were 1,2-dicarbonyls such as glyoxal, 2,3-butadione, and methyl pyruvate were several orders of magnitude slower at reacting with PM than 1,4-dicarbonyls such o -phthaladehyde and benzoquinone [120]. To reduce RCS modification of ubiquitin by 50%, an 8.8 molar excess of PM is required for HNE, a 9.3 molar excess for MGO, and a 1.31 molar excess is need for MDA [93].…”
Section: Reactive Carbonyl Species Scavengers Ameliorate Diseasementioning
confidence: 99%